2021
DOI: 10.1007/s00784-021-03902-y
|View full text |Cite
|
Sign up to set email alerts
|

Could different direct restoration techniques affect interfacial gap and fracture resistance of endodontically treated anterior teeth?

Abstract: Objectives To evaluate different direct restoration techniques on various cavity designs in anterior endodontically treated teeth (ETT). Materials and methods Ninety upper central incisors (n = 90) were selected, endodontically treated, and divided into three groups (n = 30) accordingly to the cavity design: minimal endodontic cavity access (group A), endodontic access + mesial class III cavity (group B), and endodontic access + two class III cavities (gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Moreover, Newman et al suggested that fiber posts might dissipate forces along the root canal, reducing stresses on the root and therefore preventing catastrophic failures [57]. It has also been hypothesized that, when forces exceed tolerance of the system, fiber posts might be able to concentrate stresses in the coronal portion, ultimately resulting in a repairable failure pattern [22,32]. This is also in accordance with a recent in-vivo review, which concluded that failures of fiber posts were mainly due to post loss of retention, compared to metal post that presented a higher amount of root fractures [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Newman et al suggested that fiber posts might dissipate forces along the root canal, reducing stresses on the root and therefore preventing catastrophic failures [57]. It has also been hypothesized that, when forces exceed tolerance of the system, fiber posts might be able to concentrate stresses in the coronal portion, ultimately resulting in a repairable failure pattern [22,32]. This is also in accordance with a recent in-vivo review, which concluded that failures of fiber posts were mainly due to post loss of retention, compared to metal post that presented a higher amount of root fractures [58].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Ausiello et al showed, through a FEA analysis, how a hybrid composite post should be sufficient to optimize the stress distribution, dissipating stress from the coronal to the apical end [19]. Kemaloglu et al (2015) showed that a fiber network might change stress dynamics at the interfaces [20] and recent studies suggested that this fact might influence marginal gap progression [21,22]. Different results concerning their effect on fracture resistance have been reported in literature [23][24][25], and it has been suggested that fiber reinforced materials might lower the number of clinically unrepairable fractures [26] even if ferrule effect must be considered as primary importance [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…The coronal limit of the ROI was set the coronal part of the sample, while the apical limit was set at the anatomical apex of the tooth itself. 3D manual segmentation was performed with the ROI limits, in order to separate radiopaque materials (gutta‐percha and residual cement) and voids contained inside the root canal system, as done by previous studies (Comba et al, 2021). This procedure was possible thanks to the differences in terms of greyscale values between the analyzed parts.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure was possible thanks to the differences in terms of greyscale values between the analyzed parts. Boolean operations and region growing functions were also applied to improve the quality of the segmentation, while morphological procedures were unnecessary and therefore avoided in the present study protocol (Comba et al, 2021). An exemplificative summary of the procedure is reported in Figure 1, from raw images to 3D parts.…”
Section: Assessment Of Changes In Dentin and Cement Volumes After Pos...mentioning
confidence: 99%
“…Previous studies demonstrated that bundled fibre posts exhibited intracanal adhesion as well as fracture resistance comparable to that measured for solid fibre posts (Bitter et al, 2019 ; Kul et al, 2020 ; Sturm et al, 2021 ) but with more homogeneous stress distribution (Yanik & Turker, 2022 ). Root filled maxillary central incisors with mesial and distal class III cavities restored with direct composite demonstrated comparable fracture resistance to those restored with solid and bundled glass fibre posts, and increased resistance compared to those restored without posts (Comba et al, 2021 ). In the case of weakened and flared root canals in immature teeth a combination of adhesively placed solid and bundled fibre posts contributed to fracture strength and stress distribution in vitro (Santos et al, 2022 ).…”
Section: Postsmentioning
confidence: 99%